PENGETAHUAN MAHASISWA AKPER HERMINA MANGGALA HUSADA TENTANG PENCEGAHAN STUNTING PADA BALITA: PENGETAHUAN MAHASISWA TENTANG STUNTING - Retno Winarti; Suryani Hartati (Institut Kesehatan Hermina, 2022)
Stunting in children is a health problem that must be considered and prevented early, it has a very long impact on a person's life. Prevention of stunting is carried out since the mother-to-be is in her teens. The purpose of this study is to find out the knowledge of teenagers about stunting. Cross-sectional research using consecutive sampling techniques with 101 respondents Hermina Manggala Husada nursing students. The survey was conducted using a questionnaire consisting of 10 items of questions about stunting and how to prevent it, student knowledge levels are measured using guttmen scales. The results showed that most students have good knowledge about stunting (76.93%), but most students have less knowledge about the risk factors for stunting (67.3%) and stunting impacts (48.5%). Most students get information about stunting from online media. Good adolescent knowledge of stunting prevention is the basis in preventing stunting in children as early as possible